Religious Moderation in Family Resilience: Preventing Radicalism in Indonesia’s Digital Era - Ramadhan, Suci; Zulkifli; Sonia Nawali (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2025)
The emergence of radicalism in the context of Indonesia's digital era poses a significant concern for family institutions. Family resilience systems and understanding of religious moderation values ​​are important to build simultaneously. This study examines the integration and internalization of religious moderation values within family institutions, intending to mitigate the propagation of radicalism in Indonesia during its digital era. This study employs a qualitative research method with a conceptual approach. The data utilized in this study are secondary data derived from journal articles, online mass media, books, reports, and documents obtained through literature reviews. Then, the data analysis method uses interactive qualitative based on Froma Walsh's family resilience theory. The findings of this study suggest that the notion of family resilience, grounded in the integration and internalization of religious moderation, can be operationalized through the establishment of a moderate religious system pattern, an intricate nuclear family structure, and transparent interpersonal communication. This study offers a pragmatic reference for families seeking to enhance their resilience against the threat of deviant religious beliefs in Indonesia's digital era. Furthermore, it can serve as a policy consideration regarding the internalization of religious moderation values within the family institution in the Pusaka Sakinah program at the Ministry of Religious Affairs.